2021
DOI: 10.1111/ijpo.12772
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and representativeness of body mass index in children's electronic general practice records: Linked cross‐sectional study in an ethnically‐diverse urban population in the United Kingdom

Abstract: Summary Objective To assess completeness and accuracy of children's body mass index (BMI) recorded in general practice electronic health records (GP‐EHRs). Methods We linked National Child Measurement Programme (NCMP) records from 29 839 5‐year‐olds and 26 660 11‐year‐olds attending state schools in inner London to GP‐EHRs (95% linked; 49.1% girls). We estimated adjusted odds (aOR) of at least one GP‐BMI record by sex, ethnic background, area‐level deprivation, weight‐status and long‐term conditions. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…We used real-world linked primary care and school measurement data for a 6-year period in a geographically contiguous urban area with an ethnically diverse population, representative of the wider population in NEL. We have previously shown that school measurement data provide less biased and more accurate information about child weight status than primary care EHRs 22. We excluded musculoskeletal consultations before the date of school measurement to ensure the musculoskeletal outcomes were reported after the exposure of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We used real-world linked primary care and school measurement data for a 6-year period in a geographically contiguous urban area with an ethnically diverse population, representative of the wider population in NEL. We have previously shown that school measurement data provide less biased and more accurate information about child weight status than primary care EHRs 22. We excluded musculoskeletal consultations before the date of school measurement to ensure the musculoskeletal outcomes were reported after the exposure of interest.…”
Section: Discussionmentioning
confidence: 99%
“… 32 The present findings of the lack of HCPs’ knowledge of children’s weight management services would suggest that there is even greater need to improve communication between primary care and these services. In England, few children have BMI recorded in their primary care health record 33 and there is evidence that HCPs are not good at identifying children with excess weight using observation alone. 34 The NCMP provides objective data with high national coverage, 7 , 35 therefore the integration of these data into primary care records represents a key opportunity in supporting HCPs to address child weight with parents.…”
Section: Discussionmentioning
confidence: 99%
“…We used linked school measurement programme records of weight status as we have previously shown that GP electronic health records do not contain accurate, up-to-date child measurement data and are biased to children at both extremes of the BMI distribution. 28 This resulted in exclusion of 30 552 school measurement programme participants who did not live with another school measurement programme participant in the 2013-2019 academic years.…”
Section: Strengths and Limitationsmentioning
confidence: 99%